Mortality of COVID-19 Patients Requiring Extracorporeal Membrane Oxygenation During the Three Epidemic Waves. Issue 12 (2nd October 2022) - Beyls, Christophe; Huette, Pierre; Viart, Christophe; Mestan, Benjamin; Haye, Guillaume; Guilbart, Mathieu; Bernasinski, Michael; Besserve, Patricia; Leviel, Florent; Witte Pfister, Alejandro; De Dominicis, Florence; Jounieaux, Vincent; et al.
Abstract : Clinical presentation and mortality of patients treated with extracorporeal membrane oxygenation (ECMO) for COVID-19 acute respiratory distress syndrome (CARDS) were different during the French epidemic waves. The management of COVID-19 patients evolved through waves as much as knowledge on that new viral disease progressed. We aimed to compare the mortality rate through the first three waves of CARDS patients on ECMO and identify associated risk factors. Fifty-four consecutive ECMO for CARDS hospitalized at Amiens University Hospital during the three waves were included. Patients were divided into three groups according to their hospitalization date. Clinical characteristics and outcomes were compared between groups. Pre-ECMO risk factors predicting 90 day mortality were evaluated using multivariate Cox regression. Among 54 ECMO (median age of 61[48–65] years), 26% were hospitalized during the first wave (n = 14/54), 26% (n = 14/54) during the second wave, and 48% (n = 26/54) during the third wave. Time from first symptoms to ECMO was higher during the second wave than the first wave. (17 [12–23] days vs. 11 [9–15]; p < 0.05). Ninety day mortality was higher during the second wave (85% vs. 43%; p < 0.05) but less during the third wave (38% vs. 85%; P < 0.05). Respiratory ECMO survival prediction score and time from symptoms onset to ECMO (HR 1.12; 95% confidence interval [CI]: 1.05–1.20; p < 0.001) were independent factors of mortality. After adjustment, time from symptoms onset to ECMO was an independent factor of 90 day mortality. Changes in CARDS management from first to second wave-induced a later ECMO cannulation from symptoms onset with higher mortality during that wave. The duration of COVID-19 disease progression could be selection criteria for initiating ECMO.